Plant Regeneration from Leaf Explants of Tylophora indica (Burm.F.) Merrill.: an Important Medicinal Plant - Pant, Manu; Bisht, Prabha (Indian Forester, 2011)
A procedure for the regeneration of complete plantlets of Tylophora indica from cultured leaf callus is described. Callus was obtained from leaf explants on MS medium supplemented with varying concentrations and combinations of BAP, 2,4-D and TDZ. 2,4-D (1.35Î¼M) in combination with TOZ (0.68 Î¼M) proved to be most effective for callus induction. Adventitious shoots were regenerated from surface of callus after transferring onto shoot induction medium, the optimal hormone combination being BAP (8.88 Î¼M),IAA (1.14 Î¼M) and GA, (0.58 Î¼M) giving an average of 14.25 Â± 0.62 shoots with mean shoot length 1.9 Â± 0.06 cm after 4 weeks. Individual elongated shoots were rooted on half-strength MS medium containing 2.46Î¼M IBA. The in-vitro raised plantlets with well developed shoot and roots were acclimatized successfully and shifted to field conditions with a survival rate of over 90%.